SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN DIKLAT SURABAYA - Agustina, Dwi Mutia; Sunarto, M. J. Dewiyani; Jatmiko, Kurniawan (Jurnal JSIKA, 2013)
Abstract: Work performance individual employee is very important in achieving its goal of the organization. Because of that is required the assessment system that can be relied upon, the performance of and will be used as a basis for the assessment of performance and development organization, achievement employees appropriate to a purpose in order that any employees to assess how far its performance has produced a feat that it is expected to appropriate destinations organization. Performance appraisal of civil servant, is appraisement periodically the implementation of the work of a civil servants. The assessment of performance or called dp3 or list the execution of judgments work used as an ingredient in carrying out training pns consider removal of, among others in raise in rank, training and training of, of displacement and the increase in salary ( appreciation ). Dp3 made every year ( in december ). The storage a ( 1 ) times dp3 namely for five years. For one time the promotion of employees require dp3 for 4 years. Until current value dp3 made by officials valuer of badan kepegawaian and training of surabaya limited only a record course. The absence of guidance from a supervisor toward civil servants who are worth bad. The absence of any information which explains the layout of less value of civil servants. So that employees do not know what to do and superiors also do not know in what part that should be coached Keywords: Performance Appraisal, Performance Appraisal of Civil Servant,  Badan Kepegawaian dan Diklat Surabaya.